2021
DOI: 10.1111/ced.14730
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid papulosis types D and E: a multicentre series of the French Cutaneous Lymphomas Study Group

Abstract: Background. Lymphomatoid papulosis (LyP) type D (LyP D) and type E (LyP E) have recently been described in small series of cases or isolated case reports. Aim. To further describe the clinical and histological features of LyP D and E based on a retrospective multicentre study. Methods. The clinical and histopathological features of 29 patients with an initial diagnosis of LyP D or LyP E were retrospectively assessed using standardized forms. Results. After exclusion of 5 cases, 24 patients (14 LyP D, 10 LyP E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…14 Interestingly, similar cases of atypical pityriasis lichenoides (PL) and lymphomatoid papulosis (LyP) type D and E showing double/triple expression of CD4/CD8/CD56 have been reported. [15][16][17] LyP and some cases of atypical PL (PLEVA) are part of the spectrum of CD30-positive cutaneous diseases, 18 but our case lacked a significant number of CD30-expressing cells. Both PL and LyP present as selfhealing papulonodular disseminated lesions involving mainly the trunk, bottom, arms, and legs that evolve into papulonecrotic lesions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…14 Interestingly, similar cases of atypical pityriasis lichenoides (PL) and lymphomatoid papulosis (LyP) type D and E showing double/triple expression of CD4/CD8/CD56 have been reported. [15][16][17] LyP and some cases of atypical PL (PLEVA) are part of the spectrum of CD30-positive cutaneous diseases, 18 but our case lacked a significant number of CD30-expressing cells. Both PL and LyP present as selfhealing papulonodular disseminated lesions involving mainly the trunk, bottom, arms, and legs that evolve into papulonecrotic lesions.…”
Section: Discussionmentioning
confidence: 69%
“…LyP type E consists of a rather small number of papules rapidly evolving into necrotic eschar-like lesions with a diameter of 1-4 cm and an angiocentric and angiodestructive infiltrate of neoplastic cells. 15,17 Both PL and LyP have been described in relation to MF. 16,19 On morphologic grounds, consideration should be given to primary cutaneous CD8-positive aggressive epidermotropic cytotoxic T-cell lymphoma, but this is neither CD4 nor CD56 positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Indeed, the largest series from the French Cutaneous Lymphoma Study Group (n = 29 cases of types D and E) confirmed the lack of TCRγδ expression in all cases tested. 25 Badje et al, 5 however, reported the rare occurrence of a type D case showing γδ expression, similar to some of the cases presented here. Type E LyP is associated with angioinvasion and angionecrosis, a frequent CD8+ phenotype, and sometimes epidermotropism.…”
Section: Discussionmentioning
confidence: 71%
“…Experts pathologists of the French cutaneous lymphomas study group (GFELC) [18][19][20] (BB, OH) or of the Lymphopath Network 21 (ATG, MD) reviewed cases. They recorded: localization (superficial, mid or deep-dermis, hypodermis), architecture (lichenoid (sub-epidermal band), nodular, diffuse, or interstitial (scattered cells in the dermis) pattern), size of cells, epidermotropism (in these cases, results of the blood immunophenotyping were retrieved to exclude cases with a doubtful diagnosis with Sezary syndrome), germinal centers, and associated cells.…”
Section: Histological Reviewmentioning
confidence: 99%